“This Is Going To Be Different, But It’s Not Impossible”: Adapting To Telehealth Occupational Therapy For Autistic Children - Amber Angell; Elinor Taylor; Joana Nana Serwaa Akrofi; Elaine D. Carreon; Marshae Franklin; Julie Miller; Catherine Crowley; Shona Maher (International Journal of Telerehabilitation)
This qualitative study examined participants’ experiences of transitioning to telehealth-delivered pediatric occupational therapy for autistic children during the COVID-19 pandemic. We interviewed three clinic administrators, four occupational therapists, and six parents of autistic children (n=13) from three Los Angeles area clinics over a 7-month period. Our narrative and thematic analyses yielded three overarching themes: Transformative Experiences, Reimagining Therapy, and Going Forward. Overall, we found that the transition to telehealth shifted participants’ preconceptions about themselves, their relationships, and the nature of occupational therapy. Many deepened their relationships; adapted interventions; uncovered surprising capabilities; and challenged the occupational therapy status quo to advocate for ongoing virtual delivery. Our findings bear relevance to the body of current literature debating the post-pandemic viability of telehealth-delivered occupational therapy.